Zakat Sebagai Dana Pembangunan - Listari, Kiki (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2017)
This research is an aim for the use of zakat as a development fund. The data is analyzed in a descriptive qualitative point of view. Zakat is divided into two that is fitrah zakat and maal zakat. The use of zakat is only for 8 asnaf, there are fakir, poor, amil, mu’allaf, riqab, gharim, sabilillah, ibnu sabil. From these two kinds of zakat, none of zakat can be used as development fund. except for such development for the construction of places of worship, because the construction of a place of worship is one of the eight asnaf that is allowed to receive zakat. as described in QS.At-Taubah: 60. The construction of places of worship included in sabilillah category.